CAA2015 : keep the revolution going : proceedings of the 43rd Annual Conference on Computer Applications and Quantitative Methods in Archaeology. - Campana, Stefano (Archaeopress archaeology., 2016)
This volume brings together all the successful peer-reviewed papers submitted for the proceedings of the 43rd conference on Computer Applications and Quantitative Methods in Archaeology that took place in Siena (Italy) from March 31st to April 2nd 2015.